Collective Risk Management in a Flight to Quality Episode - CABALLERO, RICARDO J.; KRISHNAMURTHY, ARVIND (Journal of Finance, 2008)
ABSTRACT Severe flight to quality episodes involve uncertainty about the environment, not only risk about asset payoffs. The uncertainty is triggered by unusual events and untested financial innovations that lead agents to question their worldview. We present a model of crises and central bank policy that incorporates Knightian uncertainty. The model explains crisis regularities such as market‐wide capital immobility, agents' disengagement from risk, and liquidity hoarding. We identify a social cost of these behaviors, and a benefit of a lender of last resort facility. The benefit is particularly high because public and private insurance are complements during uncertainty‐driven crises.